The role of PPARa in Cytochrome P450 gene expression and DNA synthesis - Jeffery, Brett (2001)
Cytochrome family P450 4A encode a major group of enzymes which are involved in the mechanism of peroxisome proliferation in rodents. Induction of CYP4A expression by peroxisome proliferators is due to transcriptional activation, mediated via the peroxisome proliferator activated receptor alpha. Cyp4a enzymes catalyse the w-hydroxylation of fatty acids and eicosanoids, and it has been suggested they thereby play a pivotal role in blood pressure regulation. Murine Cyp4a10, Cyp4a14 and Cyp4a12 genes have been reported by Bell et al (1993) and Heng, et al (1997). There is contradictory evidence in the literature concerning the expression of lauric acid hydroxylase (LAH) and Cyp4a-related protein in mouse liver and kidney. We have previously shown that Cyp4a12 is expressed at high level in a male-specific fashion in liver and kidney of mouse (Bell et al 1993). However, various workers have reported the presence, or absence, of Cyp4a proteins, or LAH, in male mouse liver. Work by Hiratsuka et al (1996) demonstrate that ddY mice show a male specific expression of LAH and Cyp4a-related protein in the liver, while other strains Balb/c and C57BL/6 exhibit no sex difference in neither enzyme or protein. In the kidney, ddY, Balb/c and C57BL/6 all show sexual dimorphism in the expression of both LAH and Cyp4a related protein. The aim of this project was to characterise the expression of mouse Cyp4a12 and resolve the conflicting results in the literature. Findings demonstrate that there is a male specific expression of Cyp4a12 in male liver and kidney. The data differs from Hiratsuka et al in that their findings present no sex difference in Balb/c and C57BL/6 expression of Cyp4a proteins. Hiratsuka et al also determined that in the kidney of ddY, Balb/c and C57BL/6 there is no sex difference in expression of neither enzyme or protein. Data here agrees with these findings and suggests that the sexual dimorphism exhibited by the LAH and Cyp4a related protein in the kidney is due to constitutive expression of Cyp4a12. Thus it appears that there is till a discrepancy between the Cyp4a12 hepatic expression pattern presented here and that of the enzyme and protein determined by Hiratsuka et al. An explanation may infer that the LAH and Cyp4a-related protein measured by Hiratsuka et al is not only Cyp4a12 but also another member of the Cyp4a family. Further work is required to establish what Cyp4a is expressed predominately in the female. Work by Henderson et al (1994) supports the case that this Cyp4a candidate may be Cyp4a10. Continuing studies will clarify the expression pattern of the Cyp4a and also investigate the mechanism of regulation of the Cyp4a family genes and the expression of male specific genes.